Factors associated with life satisfaction in Costa Rican residents aged 60 and over - Aguilar Fernández, Eduardo; Carballo-Alfaro, Ana Maricela (Población y Salud en Mesoamérica, 2023)
Introduction: Satisfaction with life is an important indicator of the quality of life of the elderly. The purpose of the study was to identify factors associated with life satisfaction in Costa Rican residents aged 60 and over. Methods: Information from a cross-sectional sample that includes 2032 participating in Costa Rica: Longevity and Healthy Aging Study was analyzed. A logistic regression model was estimated and the effect of sociodemographic variables, health status, economic situation, and support on life satisfaction was determined. Results: Life satisfaction is associated with having a partner, insomnia, the presence of more than one disability in activities of daily living, self-rated health, and the perception of the economic situation. Conclusions: Identifying factors that influence life satisfaction in people aged 60 or over, could contribute elements in the issue of generating policies aimed at establishing actions that allow improving the quality of life of this population.